(untitled) (Biodiversitas Journal of Biological Diversity, 2018)
Abstract. Sofiah S, Sulistyaningsih LD. 2019. The diversity of Smilax (Smilacaceae) in Besiq-Bermai and Bontang Forests, East Kalimantan, Indonesia. Biodiversitas 20: 379-387. The genus Smilax has taxonomic complexity problems and spacious distribution. Taxonomic study to reveal the diversity of Smilax species had been done in some regions, such as America, China, Japan, Thailand, and Indonesia. However, there is lack of information of Smilax species diversity in Kalimantan especially in East Kalimantan which lies in Sundaland biogeographic. This study was carried out to explore and record the diversity of Smilax species including the ecological and environmental data in Besiq-Bermai and Bontang forests in East Kalimantan, Indonesia. This research conducted on February and August in 2012 and July-August 2015 using exploration methods. Purposive random sampling was used to do the botanical sampling. The principal component analysis (PCA) was performed to determine the relationships between environmental components and Smilax species occurrences. There were five species of Smilax which were housed in those forests in East Kalimantan, namely, Smilax leucophylla Blume, Smilax gigantea Merr., Smilax odoratissima Blume, Smilax zeylanica L., and Smilax modesta A.DC. Smilax leucophylla and Smilax zeylanica are the most widely used by the local people for medicine. The taxonomic description, distribution, use, and vernacular name were given. The environmental factors that contribute significantly to Smilax’s growing environment are temperature and light intensity.